Analysis of complications and management of abdominal stoma - Pal, Naresh; ., Poonam; Jangra, Amit; Mishra, Vineet (International Surgery Journal, 2019)
Background: Abdominal stoma is an opening of the intestine whether temporary or permanent on anterior abdominal surgically. These are used to divert the faecal contents for safe distal anastomosis and to relieve obstruction in emergency surgeries or even in elective surgeries also. Though it is a lifesaving procedure and may be temporary or permanent. Sometimes it may result in number of significant complications which may be starting from early postoperative periods to late compilations. Methods: This is a prospective observational study, which was carried on 85 patients of abdominal stomas in the department of general surgery, Pt. B D Sharma PGIMS Rohtak. Results: In the present study there were (71) males and (14) females in the ratio of nearly 5:1. The males are 83.52% as compared females 16.47%.The commonest age group for stoma formation was in 21–30 years in either sex which is 23.52%. Numbers of males are higher in the age group of 51-60 years. The end ileostomy was made in 46 patients and loop ileostomy was in 27 patients. Oedema was seen maximally 19 patients of loop ileostomy. The other complications which are less common are retraction and ischemia of stomas. Four patients were died during treatment in this period in the present study. Conclusions: Intestinal stomas are commonly performed surgical procedure for intestinal diseases, to minimise or decrease the potential complications due to intestinal stoma meticulous attention and extreme care should be employed in preoperative and postoperative periods. Here we have provided an overview of the complications seen in formation of intestinal stomas, keeping these probable complications in mind, decision making and surgical technique continue to be remain the keys to successful stoma formation.